Green Accounting and Corporate Social Responsibility Disclosure: Financial Performance of Mining Companies in Indonesia - Ayu Anggi Anggraeni; Hayuningtyas Pramesti Dewi (Master of Accounting Universitas Trunojoyo Madura, 2022)
The purpose of this study was to examine the effect of implementing green accounting and disclosure of corporate social responsibility on the company's financial performance. This study analyzes secondary data, namely data from mining companies listed on the Indonesia Stock Exchange in 2014-2018 using simple and multiple regression analysis. The results found that the application of green accounting individually had no effect on the company's financial performance, assuming that corporate social responsibility had an effect on the company's financial performance. Simultaneously the application of green accounting and corporate social responsibility affect the company's financial performance. This research is limited to annual report data, which has not yet reached the sustainability report data. The sample is also only from one sector of mining companies. This research is beneficial for companies in managing environmental costs and carrying out their social responsibilities so that they can develop environmentally friendly companies.